A synergistic framework for curricular flexibility in online collaborative learning. Issue 2 (3rd April 2022) - Gronseth, Susie L.; Bauder, Debra K.
Abstract: Collaborative learning can be a worthwhile and valuable part of a student's online course experience, and interpersonal exchanges among members of an online course community often rely on greater intentionality within the design of the learning experience. We present a synergistic framework for strategic design of collaborative learning in the online environment, grounded in universal design for learning and facilitated through supportive technologies. The framework takes into account distance education student variability in regard to their learning, communication, abilities, and interests and incorporates curricular flexibility to mitigate barriers. Exploring relationships among key features of collaborative learning in the online environment, this conceptual article illustrates the framework through examples, strategies, and tools for two common online course activity areas—online discussions and peer teaching.